2008
DOI: 10.1111/j.1440-1827.2008.02260.x
|View full text |Cite
|
Sign up to set email alerts
|

Sebaceous carcinoma of the eyelids: Thirty cases from Japan

Abstract: Sebaceous carcinoma of the eyelids is rare in Western countries but not uncommon in Asian countries. Diagnosis is difficult both clinically and histologically. Thirty cases of sebaceous carcinoma of the eyelids treated at Tokyo Medical University Hospital were reviewed to elicit characteristic features of pathological findings. The tumor cells were infiltrating in a lobular pattern that consisted mainly of large atypical germinative cells. Sebocytes seen in the lobules had conspicuous nucleolus associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 14 publications
2
55
1
Order By: Relevance
“…In the past, Oil Red O was used to identify intracytoplasmic lipids in sebaceous lesions in fresh frozen tissue; however, standard permanent tissue processing extracts the intracellular lipids and often nonspecifically highlights macrophages and nonlipid laden cells in the background stroma. 5,6 The use of immunohistochemical markers may indeed represent a practical solution to diagnose these tumors correctly. Many studies have analyzed conventional markers such as EMA, Ber-EP4, androgen receptor, CK7, P53, etc; but, these studies have shown variable results, and the markers have mostly been analyzed individually rather than as part of a comprehensive panel.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, Oil Red O was used to identify intracytoplasmic lipids in sebaceous lesions in fresh frozen tissue; however, standard permanent tissue processing extracts the intracellular lipids and often nonspecifically highlights macrophages and nonlipid laden cells in the background stroma. 5,6 The use of immunohistochemical markers may indeed represent a practical solution to diagnose these tumors correctly. Many studies have analyzed conventional markers such as EMA, Ber-EP4, androgen receptor, CK7, P53, etc; but, these studies have shown variable results, and the markers have mostly been analyzed individually rather than as part of a comprehensive panel.…”
Section: Discussionmentioning
confidence: 99%
“…[60][61][62] Immunohistochemical staining with (Table 6) AR, CK7, CAM5.2, CD10, CD15, D2-40, EMA, and p63 had variable success. 9,12,22,42,[56][57][58][63][64][65][66][67][68][69][70] Adipophilin has been shown to be more sensitive than oil red O in detecting intracellular lipids in sebaceous carcinoma. 57,63,68 BerEP4 highlights 80% of sebaceous carcinomas, whereas negative in SCC cases.…”
Section: Sebaceous Carcinoma Versus Squamous Cell Carcinomamentioning
confidence: 99%
“…Mrozinski 25 has shown that perilipin positivity distinguishes liposarcoma from other sarcomas. For sebaceous carcinoma of the eyelids, perilipin, adipophilin, and TIP47 staining have been shown to visualize specifically holocrine secretion 24,29 and antibodies against perilipin, adipophilin, and TIP47 are already used for the immunohistochemical diagnosis of this tumor entity. In clear cell renal cell carcinoma, adipophilin expression has been correlated with good prognosis, and transcription of adipophilin may be regulated by the von Hippel-Lindau factor/ hypoxia-inducible pathway and responsible for the typical appearance of clear cell renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%